Investigation on Characteristics of Initial Rainwater Pollution in a Baijiu Enterprise - LIU Yanling; LIU Xiaodan; WANG Zhongwei (Renmin Zhujiang)
The problem of non-point source pollution caused by initial rainwater is attracting more and more attention,but the initial rainwater pollution varies in different industries.To study the characteristics of water quality pollution in the initial rainwater of Baijiu enterprises,this paper analyzes the concentration of chemical oxygen demand (COD) in the initial rainwater of different production workshops.The results show that the variation law of rainfall duration varies in different regions.The COD concentration in the koji-making workshops is higher than that in the Baijiu-making workshops.The koji powder is possibly the main pollutant in the koji-making workshops,and the dissolution of pollutants brought by the koji powder requires a certain process and time.The investigation and study on the characteristics of the initial rainwater pollution in the Baijiu enterprise can provide a basis for Baijiu enterprises to carry out non-point source pollution prevention and control in flood seasons.